2020
DOI: 10.4269/ajtmh.20-1185
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: COVID-19 and Chagas Disease in Two Coinfected Patients

Abstract: American trypanosomiasis, also named Chagas disease (CD), is an anthropozoonosis caused by the protozoan parasite Trypanosoma cruzi. The disease affects millions of people worldwide, leading yearly to approximately 50,000 deaths. COVID-19, generated by SARS-CoV-2, can lead to lymphopenia and death. We hereby describe the first report of two patients with CD and COVID-19 coinfection, from hospitalization until patients' death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
15

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 24 publications
0
26
0
15
Order By: Relevance
“…The infection caused by SARS-CoV-2 can lead to the development of a severe pulmonary and systemic disease named COVID-19 ( Alberca et al, 2020c ). Previous reports have identified that COVID-19 is often more severe in the elderly and individuals with comorbidities such as obesity, hypertension, diabetes Mellitus, other co-infections ( Alberca, 2020 ; Alberca et al, 2020a , d , f ; Castelo Branco et al, 2020 ; Shaw et al, 2020 ). Those patients generally present an increase in COVID-19-associated inflammatory markers, such as d-dimer, leukocytes count, neutrophil count, neutrophil-to-lymphocyte (NTL) ratio, alanine aminotransferase (ALT), aspartate aminotransferase (AST), and c-reactive protein (CRP) ( Wolff et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The infection caused by SARS-CoV-2 can lead to the development of a severe pulmonary and systemic disease named COVID-19 ( Alberca et al, 2020c ). Previous reports have identified that COVID-19 is often more severe in the elderly and individuals with comorbidities such as obesity, hypertension, diabetes Mellitus, other co-infections ( Alberca, 2020 ; Alberca et al, 2020a , d , f ; Castelo Branco et al, 2020 ; Shaw et al, 2020 ). Those patients generally present an increase in COVID-19-associated inflammatory markers, such as d-dimer, leukocytes count, neutrophil count, neutrophil-to-lymphocyte (NTL) ratio, alanine aminotransferase (ALT), aspartate aminotransferase (AST), and c-reactive protein (CRP) ( Wolff et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The CD patients presented an increase in COVID-19 laboratory hallmarks and a rapid disease progression. Despite the efforts of the health staff, both patients died [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with the disease have mild-to-moderate symptoms; however, approximately 15% develop severe pneumonia, while approximately 5% develop acute respiratory distress syndrome (ARDS), septic shock, and/or organ failure [ 2 ]. Lymphopenia is a recurrent feature in these patients, with a significant reduction in CD4+ T cells, CD8+ T cells, B cells, and natural killer (NK) cells [ 3 ], increasing the susceptibility of patients to severe illness and co-infection [ 4 ]. In fact, co-infections are associated with worsening of the clinical condition [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since November 2019, SARS-CoV-2 has infected over 80 million people and killed over 1.5 million people worldwide, being declared a pandemic by the World Health Organization[ 4 ]. Several comorbidities have been postulated as risk factors for severe COVID-19, such as high age[ 5 ], smoking, chronic obstructive pulmonary disease[ 6 ], obesity[ 7 ], pregnancy[ 8 ], and co-infections[ 9 ].…”
Section: Introductionmentioning
confidence: 99%